Serum Antimüllerian hormone does not predict elevated progesterone levels among women who undergo controlled ovarian hyperstimulation for in vitro fertilization - Shahryar K. Kavoussi; Shu-Hung Chen; Caitlin L. Hunn; Brady T. West; John David Wininger; Keikhosrow M. Kavoussi; Parviz K. Kavoussi (BMC, 2019)
Abstract Serum Antimüllerian hormone (AMH) has been shown to predict various in vitro fertilization (IVF) outcomes. AMH and progesterone (P) are products of granulosa cells of the ovary. Since overall granulosa cell number directly correlates with oocyte number and AMH production, the aim of this study is to evaluate whether or not serum AMH is associated with elevated P during controlled ovarian hyperstimulation (COH) for IVF. For this retrospective study, data were abstracted from charts of first IVF cycles of women (n = 201) who had undergone COH between May 2014 and May 2017. Groups were as follows: (A) AMH < 1 ng/mL (n = 32), (B) AMH 1-3.99 ng/mL (n = 109), (C), AMH ≥ 4 ng/mL (n = 60). The primary outcome measure was serum P level at trigger prior to oocyte retrieval. Mean serum P levels among groups A, B, and C were 0.92 ng/mL, 0.96 ng/mL, and 0.84 ng/mL, respectively. One-way ANOVA showed that there was no difference in mean serum P level among groups A, B, and C (p-value = 0.28). Multivariable linear regression with P as the dependent variable showed that total gonadotropin dose and peak estradiol level on day of trigger each had a significant positive relationship with P, and clinical pregnancy had a significant negative relationship. Although AMH is a predictor of certain IVF outcomes, AMH is not a predictor of elevated serum P level at trigger among women who undergo COH for IVF.